Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1093/tbm/ibac101
|View full text |Cite
|
Sign up to set email alerts
|

Rapid-cycle designs to adapt interventions for COVID-19 in safety-net healthcare systems

Abstract: Racial/ethnic minority, low socioeconomic status, and rural populations are disproportionately affected by COVID-19. Developing and evaluating interventions to address COVID-19 testing and vaccination among these populations are crucial to improving health inequities. The purpose of this paper is to describe the application of a rapid-cycle design and adaptation process from an ongoing trial to address COVID-19 among safety-net healthcare system patients. The rapid-cycle design and adaptation process included:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Our researchpractice partnership uses a multipronged community engagement approach to (1) identify research questions, (2) develop, adapt and implement interventions and (3) inform dissemination plans. 18 19 The community engagement approach includes a weekly project meeting with AUCH, UDHHS and the research team and quarterly Patient Advisory Committee (PAC; consisting of CHC patient representatives) and Study Advisory Committee (consisting of patients, CHC staff, UDHHS and AUCH representatives) meetings. The research objectives of SCALE-UP II were identified in partnership with AUCH and UDHHS; both AUCH and UDHHS were interested in addressing the impact of COVID-19 among historically marginalised communities in Utah.…”
Section: Methods and Analysismentioning
confidence: 99%
“…Our researchpractice partnership uses a multipronged community engagement approach to (1) identify research questions, (2) develop, adapt and implement interventions and (3) inform dissemination plans. 18 19 The community engagement approach includes a weekly project meeting with AUCH, UDHHS and the research team and quarterly Patient Advisory Committee (PAC; consisting of CHC patient representatives) and Study Advisory Committee (consisting of patients, CHC staff, UDHHS and AUCH representatives) meetings. The research objectives of SCALE-UP II were identified in partnership with AUCH and UDHHS; both AUCH and UDHHS were interested in addressing the impact of COVID-19 among historically marginalised communities in Utah.…”
Section: Methods and Analysismentioning
confidence: 99%